Study on the Carbon Footprint Reduction Through Recycling Activities in UTHM: Effect of COVID-19 Pandemic - Abdul Kadir, Aeslina; Choo, Zhe Jian; Sarani, Noor Amira; Hassan, Mohd Ikhmal Haqeem; Mohajerani, Abbas (International Journal of Sustainable Construction Engineering and Technology, 2022)
Recycling is an excellent method to manage institutional solid waste and reduce the environmental carbon footprint. However, the outbreak of the COVID-19 pandemic has caused unprecedented chaos and affected recycling activities in UTHM. Therefore, the trend of carbon reduction through recycling activities in UTHM was determined to investigate the impact of the COVID-19 pandemic on the trend of carbon reduction. The data was collected from the recycling center in UTHM and the carbon reduction was further calculated to compare the difference before and after the pandemic outbreak. The weight of paper products collected was the highest, accounting for more than 75%, while the weight of aluminium collected was the lowest, accounting for less than 1%. Furthermore, it was found that the trend of carbon reduction increased steadily in 2019. However, the outbreak of the COVID-19 pandemic has caused the trend to plunge and approach zero in March 2020. Nevertheless, once the COVID-19 pandemic was under control, the carbon reduction trend improved and peaked again in 2021. In addition, paper products achieved the highest of the total carbon reduction at 5143.072 tCO2e while aluminium was the lowest at 0.357 tCO2e. The highest total carbon reduction was achieved in 2019 with 1980.168 tCO2e while the lowest was recorded in 2020 with 1220.932 tCO2e. As a result, the Covid-19 Pandemic had a significant impact on the recycling rate in UTHM, which resulted in a reduction in the total amount of carbon reduction.